Qualitative Study of Long-Haul Truck Drivers' Health and Healthcare Experiences. Issue 3 (March 2021) - Johnson, Jennifer K.; Vingilis, Evelyn; Terry, Amanda L.
Abstract : Objective: Long-haul truck drivers suffer increased health risk, but how they use healthcare is unknown. The objectives of this study were to explore the health experiences of these drivers, their healthcare experiences, and their relationship with their main medical provider. Methods: In-depth semi-structured interviews were conducted with 13 Canadian long-haul truck drivers. The majority (85%) were men and recruited at a truck stop on a major transport corridor between Canada and the United States. Results: Through phenomenological analysis of the transcribed interviews, themes of perseverance, isolation, dehumanization, and working in a hidden world emerged as major influences on the health experiences of these drivers. Barriers to their medical provider were also revealed. Conclusions: Continuous exposure to a stressful work environment and inadequate access to primary care likely negatively affect the health of long-haul truck drivers. Given the experiences of this small group of drivers, improved healthcare and health resource availability might mitigate the risk of this occupational group. Abstract : Supplemental Digital Content is available in the text